Community Participation of Native Plant Conservation and Restoration Ban Khao Wang Head Watershed Community, Nakhon Si Thammarat Province - Pakdeenarong , Pinpetch; Kotchasaengsan, Rachada (Area Based Development Research Journal, 2021)
The objectives of this research were to develop community participation models for native plant conservation and restoration and suggest guidelines for the learning process scheme in alignment with the community’s context while raising awareness of the native plants’ value. The target group was community officials, community leaders, and youths. This participatory action research (PAR) is directed toward establishing a participatory learning process between the research team and the community. The community activities were simultaneously conducted along with data collection, focus group discussion, in-depth interview, survey, and workshops. The results revealed that the community participation model in the conservation and restoration of native plants was well-suited for the community’s context. Activities included restoring the ecosystem around the community’s head watershed, determining and declaring the conservation area of plants and aquatic animals, conserving plants on the creek, planting in integrated gardens, issuing rules to regulate the use and study of nature in the community’s forest area, propagating native plants and adding value. Guidelines of the learning process to build conscience and raise awareness of native plants’ value included the community’s collaboration in creating the native plants’ database, effectively maximizing the native plants’ value, developing a learning area on native plants, and local wisdom in using them, and organizing activities to promote community’s learning process and participation. As a result, the community has become more aware of the value of native plants, participate in community ecosystem conservation and restoration activities, develop learning areas on native plants and local wisdom, process value-added products, and extending Suan Som Rom integrated gardens.